Assessment of the Educational and Health Care System–Related Issues From Physicians' and Nurses' Perspectives Before Developing a Palliative Care Program Within the Palestinian Health Care System: A Cross-sectional Study. Issue 3 (28th January 2022) - Abu-Odah, Hammoda; Molassiotis, Alex; Liu, Justina Yat Wa
Abstract : A scarcity in research assessing the palliative care (PC) educational and health care system–related issues has been reported in the Middle East region; the region comprises a wide range of economically diverse countries. Discrepancies across countries have created difficulties in adopting other countries' experiences. This study aimed to assess PC knowledge, attitude, educational needs, and health care system–related issues from physicians' and nurses' perspectives before developing PC services within the Palestinian health care system. One hundred sixty-nine professionals participated in this cross-sectional survey. Data were collected by validated instruments. Professionals had insufficient knowledge about PC, but they had positive attitudes toward end-of-life care and care of the dying. Patients'/families' avoidance of talking about issues around dying and lack of training for staff related to PC were the most 2 significant barriers to providing PC. Educational level and previous training were found to be associated significantly with knowledge and attitudes toward PC. Study conclusions support the recommendation for integration of education about PC within the health curricula and in-service training and should cover the basic and advanced principles of PC and symptom management.